A Note on Effect of Storage of Date Palm (Phoenix dactylifera L.) Pollen Grains on Their Germination and Date’s Fruit Setting (University of Khartoum Journal of Agricultural Sciences, 2023)
This investigation was initiated to study the effect of differentstorage methods on in vitro germination of date palm pollen grains as wellas on fruit-setting. The collected pollen grains were stored in arefrigerator, freezer and freezer after being immersed in liquid nitrogen.After one year of storage, pollen viability was evaluated in terms of invitro germination percentage and fruit-setting. The results revealed thatthe highest germination percentage and fruit-setting were associated withfresh pollen grains stored in the freezer followed by storage in freezerafter immersion in liquid nitrogen and storage in the refrigerator. Theseresults indicated that well dried pollen grains could be stored in fairlyviable state until the following season in a freezer or a refrigerator.
Keywords: Date palm; pollen storage; pollen germination; fruit set